Fracture of the humeral bone as the first clinical presentation of metastatic papillary thyroid carcinoma in Ibadan (2019)
Papillary thyroid carcinoma is the commonest type of thyroid cancer representing 75 to 85 per cent of all thyroid cancer cases. It is often well-differentiated, slow-growing, and localized, although it can metastasize. This is a case of a 49-year-old male who presented with a pathological fracture of the left humerus. A bone biopsy was done at the surgery which had a histological diagnosis of metastatic thyroid carcinoma. A total thyroidectomy was subsequently done and was histologically reported as a follicular variant of papillary thyroid carcinoma. The patient was clinically stable post thyroidectomy and was discharged home on the 10th postoperative day and he is currently being followed-up in the surgical outpatient clinic. Pathological fracture as the initial clinical presentation is an unusual manifestation of metastatic thyroid carcinoma; therefore a high index of suspicion is needed to make this diagnosis. In any patient presenting with a pathologic fracture, the possibility of metastatic carcinoma from the thyroid gland should always be considered.